Eksposisi Ajaran Tasawuf Sunan Muria: Konstruksi dan Kontekstualisasi Sufisme Jawa - Arafat, Ahmad Tajuddin; Adlina, Atika Ulfia; Rosyida, Hanik (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
One of the Walisongo figures who is interesting to look at further in the map of spreading Islam in Java is Raden Umar Said or better known as Sunan Muria. The histories of Sunan Muria itself are based more on stories and folklores that have inlined from generation to generation in the traditional Muslim community around Mount of Muria rather than based on literature and manuscript notes. To fill this empty information space, researchers conducted a study of the intellectual transmissions and teachings of Sunan Muria's mysticism (Sufism) using folklore and cultural anthropology approaches. As a result, the variety of folklores and values of life ​​that internalized in the Muslim community around Mount of Muria at least inherited in two ways. First, collective recognition as part of the Islam missionary of Sunan Muria which is realized by preserving existing of traditions and sacred graves, as well as the importance of connecting people to the intellectual transmission chain that continues from Sunan Muria to the other saints or Wali regarding with Islamization in Java. Second, religious attitudes and values that are strong with the values ​​of humanity, tolerance, moderation, integrity in purifying soul and exercising the inner being or mental health. Teachings that are in line with the conception of Sufism teachings based on practices that known as Akhlaqi Sufism.